2011
DOI: 10.1103/physrevb.84.035110
|View full text |Cite
|
Sign up to set email alerts
|

Topological Anderson insulator phenomena

Abstract: We study the nature of the disorder-induced quantized conductance, i.e., the phenomena of topological Anderson insulator (TAI) induced in HgTe/CdTe semiconductor quantum well. The disorder effect in several different systems where anomalous Hall effect exist, is numerically studied using the tight-binding Hamiltonian. It is found that the TAI phenomena also occur in the modified Dirac model where the quadratic corrections k 2 σ z is included and electron-hole symmetry is kept. It also occurs in the graphene sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 46 publications
2
69
0
Order By: Relevance
“…The different bulk band gap responses at K and K ′ are consistent with the tightbinding result discussed in Ref. [18].…”
Section: Robustness Of Quantum Anomalous Hall Effect a Staggeredsupporting
confidence: 90%
“…The different bulk band gap responses at K and K ′ are consistent with the tightbinding result discussed in Ref. [18].…”
Section: Robustness Of Quantum Anomalous Hall Effect a Staggeredsupporting
confidence: 90%
“…25,26 TAI has been investigated in more related models, such as Haldane model, KaneMele model and 3DTI model. [27][28][29][30][31][32] It is indicated that TAI is dependent on the type of disorder, for example, TAI phase is absent for the magnetic disorder and spatially correlated disorder. 33,34 On the other hand, gapped and gapless topological phases and transport characteristics in layered structures and thin films have been studied recently in the presence and absence of disorder.…”
Section: Introductionmentioning
confidence: 99%
“…For numerical calculation, the tight-binding representation of the four-band Hamiltonian on square lattice is used. [24][25][26] To realize the QAH phase, magnetic doping is needed to break the TRS between the two spin blocks. When one spin block is in normal insulting regime, but the other is topological nontrivial, QAH state appears, resulting in nonzero net Hall conductance.…”
mentioning
confidence: 99%